Indicators of gender violence in romantic relationships. Case study in chilean adolescents - Maria Cruz Sánchez Gómez; Beatriz Palacios Vicario; Antonio Victor Martín García (Sociedad Iberoamericana de Pedagogía Social, 2015)
The presence of gender violence is increasing alarmingly in our society and has become one of our most serious social problems. The data indicate that the origin of much of this type of behaviour has its roots in early adolescent relationships, in which the presence and repetition of chauvinist patterns and models has been verified. In this paper we assume that this kind of conduct is related to socially accepted behaviours that form part of the normative patterns typical of socialization processes. To analyse this thesis, an interdisciplinary group of researchers from Spanish and Chilean universities    carried out a qualitative study on behaviours associated with gender violence in groups of adolescents and young people from different economic, geographic, social and ethnic contexts in order to gather evidence about the ways adolescents establish romantic or intimate relationships and to determine whether there are any indications of male chauvinist violence against adolescent women. The research design proposed takes as a reference the principles of Grounded Theory and employs the constant comparative method, that is, the information is collected, coded and analysed simultaneously, with theoretical sampling that involves selecting new cases as a function of their potential to help refine or expand the concepts and theories already developed. Thus, the coding of the discourse was carried out using open coding, axial coding and selective coding, and finally grouping the relevant categories or ideas into meta-categories to build the theoretical schema. Participating in the study were 156 adolescents (77 girls and 79 boys) residing in the urban area of the Arica region in Chile, having been selected according to the variables "academic year" and "age". Seventeen discussion groups were formed until data saturation was attained. The findings show that in these first adolescent dating relationships there is an important number of negative references and references to violent chauvinist behaviour, in particular psychological violence, in which there is a clear, rigid, culturally assimilated structuring of gender roles in which the values of strength, power and dominance appear as belonging to a masculine identity. These "values" are at the basis of structures of inequality, and one means of attaining them and defending them is through aggression. In contrast, female identity is constructed with the attributes of weakness, control and need for protection. These values are transmitted as norms of desirable behaviour and are inserted into the very identity of adolescent women. Finally we discuss the need for greater institutional resolve in the improvement of equality programs and the development of educational proposals to enable intervention programs to be designed and prioritized. This should be done with a view to promoting more egalitarian dating relationships in adolescence and young adulthood, as a means to educate for prevention of abusive behaviour in adolescent dating and the construction of non-aggressive love relationships.